Peningkatan Keterampilan Menyimak Peserta Didik dengan Menggunakan Model Discovery Learning pada Tingkat Sekolah Dasar - Syarifah Rahmayani; Sila Angraini; Gusmaneli Gusmaneli (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Listening skills are very influential on learning success. Successful learning can run well if students are able to capture messages or information related to the teaching material presented by educators or from reading material. Listening as a learning process is carried out in an integrated manner and receives the same attention as other language skills. However, in reality, most of the listening lessons delivered by educators in elementary schools in particular are still often ignored. In the learning process, educators use learning media, namely less innovative learning media in the form of pictures contained in theme books. Educators still use theme books and worksheets as learning resources and media without any other learning media that can attract students' attention. However, the use of this learning media does not attract students' attention and interest in learning because learning seems boring for students. As a result, many students lack concentration in learning and students are less active in the learning process. Therefore, the author uses the Discovery learning method, which is expected to foster concentration and attract students' attention so that students' listening skills can improve as expected.